1992
DOI: 10.1038/hdy.1992.20
|View full text |Cite
|
Sign up to set email alerts
|

Segregation and fertility in Mus musculus domesticus (wild mice) heterozygous for the Rb(4.12) translocation

Abstract: Analysis of the progeny of wild mice heterozygous for the Rb(4.12) shows that fertility and segregation are normal. This study, and others with similar results, suggests that our view of the chromosomal evolution of the house mouse should be revised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
6

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 14 publications
(15 reference statements)
0
14
0
6
Order By: Relevance
“…In some instances a single heterozygous rearrangement may be sufficient to adversely affect fertility (Hauffe & Searle 1998), while in others those carrying few heterozygous rearrangements do not generally show a decrease in fertility (Winking et al 1988, Viroux & Bauchau 1992, Wallace et al 1992). On the contrary, however, hybrids heterozygous for more than three rearrangements generally show elevated levels of aneuploidy and/or germ cell death (Redi & Capanna 1978, Saïd et al 1993.…”
Section: Chromosomal Speciation In Microgalementioning
confidence: 97%
“…In some instances a single heterozygous rearrangement may be sufficient to adversely affect fertility (Hauffe & Searle 1998), while in others those carrying few heterozygous rearrangements do not generally show a decrease in fertility (Winking et al 1988, Viroux & Bauchau 1992, Wallace et al 1992). On the contrary, however, hybrids heterozygous for more than three rearrangements generally show elevated levels of aneuploidy and/or germ cell death (Redi & Capanna 1978, Saïd et al 1993.…”
Section: Chromosomal Speciation In Microgalementioning
confidence: 97%
“…Field and laboratory studies on structural heterozygotes derived from wild popula- tions have shown that the presence of one, two or three trivalents at meiosis may have little effect on fertility Scriven, 1992;Viroux and Bauchau, 1992;Wallace et al, 1992). In contrast, many trivalents, in multiple single heterozygotes or long chains or rings in complex heterozygotes, may reduce fertility to the point of sterility.…”
Section: Effectiveness Of the Post-mating Barriermentioning
confidence: 99%
“…Our results indicate that neither meiotic disjunction nor hybrid sterility or hybrid breakdown exists between the reciprocal crosses of the two karyotypes investigated here or among the backcrosses of these hybrids. Although our study is not unique in reporting the lack of a hybrid disadvantage between different kayotypes with centric fusions (Nachman & Meyers, 1989; Viroux & Bauchau, 1992; Hauffe & Searle, 2002), the large difference in the diploid number between the two S. campestris karyotypes (2 n =32 and 2 n =46) is exceptional. For instance, the diploid number in the rodent Holochilus brasiliensis reported by Nachman & Meyers (1989) ranged from 48 to 52, while the variation in the diploid number in the case of the mole rat Spalax ehrenbergi was 52–60 (Nevo, Filippucci & Beiles, 1994).…”
Section: Discussionmentioning
confidence: 73%
“…However, litter size was constant for our crosses (Table 2A), indicating that neither the karyotypic hybrids nor their offspring suffered any disadvantage when compared with the pure lines. Reduced litter size occurs in chromosomal heterozygotes of M. musculus (Said et al ., 1993; Hauffe & Searle, 2002), as well as in other rodents (Theiler & Blanco, 1996), but not in litter sizes of karyotypes in the centric fusion system of M. musculus hybrid zones (Britton‐Davidian et al ., 1990; Viroux & Bauchau, 1992; Hauffe & Searle, 2002). Clearly, the karyotypic composition of an individual is not sufficient to affect litter size: other conditions need to apply in addition to a hybrid karyotype (Hauffe & Searle, 2002).…”
Section: Discussionmentioning
confidence: 99%